HUBUNGAN POLA MAKAN DAN KEBIASAAN KONSUMSI KOPI DENGAN KEJADIAN GASTRITIS PADA USIA DEWASA DIMASA PANDEMI COVID 19 DI PUSKESMAS JATIASIH - Afifah Afriana (2022)
Gastritis is a health disorder characterized by inflammation of the gastric mucosa. Irregular eating patterns and increased coffee consumption are risk factors for gastritis during COVID-19 pandemic. The purpose of this study was to determine the relationship between eating patterns and coffee consumption habits with the incidence of gastritis in adulthood during the covid 19 pandemic at Jatiasih Health Center. The research design is quantitatively with a cross sectional approach. The sampling technique in this research is purposive sampling with 165 respondents. Analysis of the data used in this research is Chi-Square Test. The results of the statistical test found a significant relationship between diet and the incidence of gastritis with p-value (0.012) and significant relationship between coffee consumption habits and the incidence of gastritis with p-value (0.011). This research can be used as a source of information for the community in preventing gastritis, for health workers it can be used in nursing care and for further research it can be used as a research reference with different risk factors.